2000
DOI: 10.1016/s0022-5347(05)67857-3
|View full text |Cite
|
Sign up to set email alerts
|

The Modern Endoscopic Approach to Ureterocele

Abstract: With the use of modern endoscopic techniques children with intravesical and single system ureteroceles require secondary open surgery less frequently than those with ectopic and duplex system ureteroceles. The mode of presentation does not predict the need for a repeat open procedure. Thick walled ureteroceles require repeat endoscopic puncture more frequently than thin and intermediate walled ureteroceles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(19 citation statements)
references
References 10 publications
2
11
0
6
Order By: Relevance
“…Regardless the technique used, the only encountered and described complication, was new-onset Vesicoureteral Reflux (VUR) into the punctured system. Reported rates of postoperative VUR ranged from 18 to 27% [1][2][3][4]6,8] one have to be very careful using new techniques for endoscopic treatment and have to take into consideration that possible complications may overweight the advantages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless the technique used, the only encountered and described complication, was new-onset Vesicoureteral Reflux (VUR) into the punctured system. Reported rates of postoperative VUR ranged from 18 to 27% [1][2][3][4]6,8] one have to be very careful using new techniques for endoscopic treatment and have to take into consideration that possible complications may overweight the advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic puncture/incision is currently suggested as the first line treatment for ureteroceles, especially those associated with single system and intravesical ureteroceles. The timing of endoscopic intervention toward earlier periods has been noted [1][2][3][4][5][6][7][8]. Recently transurethral laser incision of ureterocele has been proposed as a safe and efficacious option [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Husmann et al [5] demonstrated that high-grade reflux or greater than 2 renal units-associated reflux necessitated a repeat open procedure in 96% of cases. Although new onset reflux is likely to be persistent, it is most often low grade and asymptomatic so that patients can be followed nonoperatively in the cases of small incision [6,7,8]. Castagnetti et al [9] reported a 32% occurrence rate, but reflux in ureterocele moiety was the indication for operation only in 5% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Yüzde 75 olguda alt pole reflü olduğu için nonfonksisyonel üst pol eksizyonunun yeterli olmayacağı kanısı yaygındır (13) . Dolayısı ile alt üriner sistemde ektopik yerleşimli üreterosel eksizyonu, mesane tabanı rekonstrüksiyo-nu ve reimplantasyon ile onarım sıklıkla tercih edilen uygulamalardır (15) . Heminefrektomi gibi üst üriner sistem girişimlerinden sonra preoperatif mevcut olan vezikoüreteral reflüye bağlı alt sistemde reoperasyon gerekmektedir (9) .…”
Section: Discussionunclassified